Comparative study of body composition and anaerobic performance between football and judo groups - Triki, M.; Rebai, H.; Abroug, T.; Masmoudi, K.; Fellmann, N.; Zouari, N.; Tabka, Z. (Science & Sports, 2012)
Aim: To compare the impact of the practice of football and judo on body composition and anaerobic performance of prepubertal boys. Methods: Thirty-two footballers, 32 judokas and 32 control subjects achieved a measure of body composition using the skin folds method. They performed the Squat-jump test, the Countermovement jump and the Wingate test to determine their anaerobic performance. Results: The lean mass (kg) of footballers and judokas was similar but higher than the control group (p = 0.001). Fat mass (kg) of controls was higher than footballers (p = 0.023). There was a significant difference for specific power (W/kg) related to total body mass in Squat-jump between footballers and other groups (p = 0.0057). The specific power (W/kg) in Countermovement jump was higher in footballers than judokas (p = 0.000012). Specific power (W/kg) measured during Wingate test was similar between footballers and judokas. There was no significant difference in the peak power (W/kg) between all groups when it is related to the lean mass. Conclusion: This study shows that footballers are more powerful than judokas and controls in the tests Squat-jump and Countermovement jump. Peak power of footballers and judokas is similar when it is related to lean mass.